Brief Dataset on produced handsheet from oil palm residue lignocellulose treated with Bacillus cereus on mechanical and physical characterization - Syarifah, Sharfina Mutia; Mohd Kassim, Angzzas Sari; Mohd Aripin, Ashuvila; Chee, Ming Chan; Zainulabidin, Muhd Hafeez; Ishak, Nadiah; Siswanto, Waluyo Adi (Elsevier, 2021)
This article presents experimental data on oil palm biomass (oil palm leaves, oil palm trunk and empty fruit bunch) handsheet production characterization by biodelignification treatment using Bacillus cereus extracted from termite gut ( Coptotermus curvignathus ). It associates the lignocellulose chemical composition obtained via technical association pulp and paper industry TAPPI T 222 om-02 testing on lignin con- tent reduction determination, holocellulose and hemicellu- lose content determination (Kurscher-Hoffner method). Sev- eral data obtained for handsheet characterization presents brightness, opacity, contrast ratio, din transparency, thick- ness, bursting and tearing indexes are collected. Handsheet surface morphology was also observed on ratio of gaps differ- ences between fiber bonding conducted using scanning elec- tron microscope (SEM) and ImageJ software. The raw data findings supplement chemical composition analysis for both untreated and treated substrates on handsheet quality per- formance check as presented in the research article “Bio- Mechanical Pulping of Bacteria Pre-Treatment on Oil Palm Biomass for Handsheet Production”[1] . For understanding correlations into the difference among lignocellulose content composition which affect the handsheet formation and me- chanical strength refer to article from this research [1] . This dataset is made publicly available for optimizing alternative waste material reuse in the pulp and paper industrial section.